Insomnia and poor sleep quality in refugee and asylum-seeking populations: A systematic review and meta-analysis - Lucca Passow Carpinelli; Luis Eduardo Gauer; Victor Henrique Dominiak Soares; Simone Blythe Williams; Caroline Baldini Szepeilewicz; Julia Valle Pezzini; Antônio Oesir Gonçalves Neto; Sidarta Tollendal Gomes Ribeiro (PLoS ONE, 2026)
Refugees and asylum seekers face significant mental health challenges, yet sleep disturbances remain underrecognized despite their critical impact on well-being. This systematic review and meta-analysis assessed sleep quality and insomnia severity across 66 studies (n = 42,956). Pooled analyses of the Insomnia Severity Index (ISI) and Pittsburgh Sleep Quality Index (PSQI) based on studies identified in Cochrane, Embase, and PubMed from database inception to December 2024 revealed clinically significant sleep disturbances. The pooled mean ISI score (13.76, 95% CI 10.39–17.13) falls within the upper end of the subthreshold range, bordering on moderate clinical insomnia, while PSQI scores (8.59, 95% CI 2.11–15.07) exceeded clinical thresholds for poor sleep. The pooled prevalence of sleep adversities was 43.2% in adults and 36.4% in children. Secondary findings highlighted prolonged sleep latency and frequent nightmares. Although subgroup analyses suggested trends across populations and assessment methods, statistical significance was limited by sample heterogeneity. Standardized sleep assessments must be integrated into refugee health protocols, with targeted interventions addressing insomnia risk factors.